Mutu fillet ikan nila (Oreochromis niloticus) pada fase post mortem dengan pengawet dari ekstrak biji picung (Pangium edule Reinw) pada penyimpanan suhu dingin - Aris Munandar; Yanti Febrisari; Sakinah Haryati; Dini Surilayani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
Tilapia fillets are produced to be easier to process and are expected to increase fish consumption. Tilapia fillets with the addition of 60% picung seed extract had a post-mortem phase of 13 days. Picung seeds serve as preservatives because they contain antibacterial alkaloids, flavonoids, and tannins. Therefore, the quality of tilapia fillets with the addition of 60% picung seed extract needs to be studied. This study aimed to determine the quality of tilapia fillets during the post-mortem phase. ilapia fillets soaked in picung seed extract 60% for 30 minutes and stored at cold temperatures. Tilapia fillet quality parameters include pH, Total Plate Count (TPC), Total Volatile Base (TVB), and organoleptic Test (appearance, smell, and texture). Observations were conducted in the pre-rigor phase (1st day), rigor mortis (6th day), early post-rigor (10th day), and late (13th day). Data analysis was done by complete randomized design. The pH of the tilapia fillet in the pre-rigor to post-rigor phase is 6.34-6.45. The value indicates that the fillet is still of good quality. Based on TPC and TVB values, tilapia fillets have good quality until the sixth day (rigor mortis). TPC value in that phase is smaller than 5 x 10-5, 1.54 x 10-4 colonies/mL, while the TVB value is 22.24 mg N/100 g smaller than the standard (30 mg N/100 g). The parameters of appearance, smell, and texture have a value of more than 7 in the rigor mortis phase. The organoleptic value showed that tilapia fillets were of good quality until the rigor mortis phase for six days. Tilapia fillets have good quality until the rigor mortis phase based on SNI 2729: 2013). Such tilapia fillets have a shelf life and can be consumed until the sixth day.